Best practices for fishing sustainability : fishing gear assessment in the Newfoundland inshore northern cod fishery - Rouxel, Yann, 1991- (2017)
From the biggest fishery collapse in the history to a recent and limited reopening, the northern cod fishery of Newfoundland is now facing significant issues regarding its ecological and economic sustainability. Major pivotal factors influencing resource sustainability involve the predominant use of gillnets as the main fishing method and the perception of Atlantic cod as a low value commodity product. By considering gillnetting and two other fishing methods used in this fishery, handlines and Newfoundland cod pots, we identified strengths and weaknesses of each harvesting method as a basis for best practices management decisions. This assessment involves multi-criteria evaluations based on “ideal gear properties” identified by the International Council for the Exploration of the Sea (ICES) that was adapted to incorporate additional criteria based on data specific to this fishery and harvesting methods. An index scoring system involving 20 ecological, economic and social criteria was developed and used to assess the three gears. Catch related data were collected onboard commercial fishing vessels during 7 days of fishing and 15 structured interviews with fishermen were conducted in the economic and social criteria assessment. Literature reviews were also conducted to supplement these data. Handlining obtained the best results on each of the three main categories, with significant advantages with regard to collateral impacts on the marine ecosystem as well as economic and social incentives for an adaptive and accessible cod fishery. Newfoundland cod pots were evaluated with the second overall best results, offering benefits for cod population composition and interesting work conditions. Although this device presented economic disadvantages, Newfoundland cod pots ensure best quality of catches and therefore are an interesting option for a quality-based fishery. Though being the fishing gear the most widely in use by cod fishermen, bottom-set gillnets are the least sustainable fishing method. Its catch related ...